2009
DOI: 10.1007/s13312-010-0062-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of dot enzyme immunoassay (Typhidot-M) and Widal test in the diagnosis of typhoid fever

Abstract: We compared the sensitivity and specificity of Typhidot-M and Widal test with blood culture (gold standard) for diagnosing typhoid fever in 105 children aged 1-15 years admitted with clinical suspicion of typhoid fever. Of the 105 cases, blood culture was positive for S.typhi in 41 (39%) children, Widal test was positive in 48 (45.7%) and Typhidot-M was positive in 78 (74.3%) cases. Sensitivity and specificity of Typhidot-M was 92.6% and 37.5% while sensitivity and specificity of Widal test was 34.1% and 42.8%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
32
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 7 publications
(3 reference statements)
7
32
0
1
Order By: Relevance
“…[17][18] This study showed that IgM anti S. typhi serologic test had a poor AUC when cut-off value ≥4 was used, while highest AUC was demonstrated on cut-off value >8. Sensitivity was found to be good as reported in previous studies in all age groups6 and children group, 10,11 reflecting the high number of positive result when the disease is actually present. In contrast, its specificity was considered low; meaning that it would give a low number of negative results when the disease was actually not present.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…[17][18] This study showed that IgM anti S. typhi serologic test had a poor AUC when cut-off value ≥4 was used, while highest AUC was demonstrated on cut-off value >8. Sensitivity was found to be good as reported in previous studies in all age groups6 and children group, 10,11 reflecting the high number of positive result when the disease is actually present. In contrast, its specificity was considered low; meaning that it would give a low number of negative results when the disease was actually not present.…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, its specificity was considered low; meaning that it would give a low number of negative results when the disease was actually not present. High sensitivity and low specificity of the test were also reported in the childrenpopulated study performed by Narayanappa, et al 11 This retrospective study was a hospitalbased study where most patients had previously visited the primary health care. Children with 1-14 days of fever were included because the best period of blood culture are the first few days of disease [14][15][16] and the best period of IgM anti S. typhi serologic test is the second week of disease.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In clinical studies involving small cohorts of hospitalized patients, both the Typhidot and TUBEX tests have demonstrated good performance in clinically suspected typhoid fever cases in comparison to the Widal test, particularly in early infection (Bhutta & Mansurali, 1999;House et al, 2001;Jesudason et al, 2002;Olsen et al, 2004;Begum et al, 2009;Narayanappa et al, 2010). In larger studies both in Asia and Africa, the new generation serological tests have compared less favourably Ley et al, 2011).…”
Section: Serological Testsmentioning
confidence: 99%
“…Moreover, blood culture is prohibitively expensive in most settings where typhoid fever is endemic.Serodiagnosis of typhoid fever has been attempted since 19th century when Widal and Sicard showed that serum of patients with typhoid fever agglutinate typhoid bacilli. 8 Therefore, diagnosis and treatment of typhoid fever in endemic and resource-constrained settings is commonly done on the basis of clinical presentation or a positive Widal test, which has suboptimal sensitivity and specificity [9][10][11] .Isolation of serotype type from blood remains the method of choice for the laboratory diagnosis. Widal test is the mainstay in the diagnosis of typhoid fever in most laboratories but it has drawbacks .…”
Section: Introductionmentioning
confidence: 99%